What a Beast ! : A look-it-up guide to the monsters and mutants of Mythology - Kelly, Sophia; Hansen, William (New York : Scholastic, 2010)
Describes some of the creatures and monsters in Greek mythology.
Keywords: Monsters-- Encyclopedias -- Juvenile literature; Mythology, Greek -- Encyclopedias , -- Juvenile literature